Daya Tetas Telur Aedes aegypti pada Berbagai PH Air Limbah Domestik - I Gede Dedy Suwartawan; Retno Hestiningsih; Martini Martini; Ari Udijono; Siswi Jayanti (Jurnal Riset Kesehatan Masyarakat, 2021)
Vector control of the Aedes aegypti mosquito in the pre-imago stage is strategy to reduce dengue infection. The aim of this study was to analyze the difference domestic sewage water pH to the hatchability of Ae. aegypti. This was an experimental study with a posttest only control group design. Independent variables  were domestic sewage water media with pH of 6.5, pH of 7.5, pH of 8.5, and pH of 9.5 and dependent variable was egg hatchability of Ae. aegypti. The results showed that the most average number of Ae. aegypti eggs hatched into larvae was at pH 7.5 with  40.68% and the lowest at pH 5,5 with 0%. The results of the Kruskal Wallis test showed that there were differences in the pH of domestic sewage water to the hatchability of eggs of Ae. aegypti (p = 0.001). The results of the Mann–Whitney U test showed that there was a significant difference between the number of egg hatched in the pH of domestic sewage water at pH of 5,5. Research proves that the eggs of Ae. aegypti is able to hatch in domestic liquid waste media with  pH range at pH of 6,5 – pH of 9,5. In the future Aedes aegypti mosquito control program is not only focus on clean water container water but also on the environment, especially drainage which has the potential to become a breeding place for Ae aegyptiKeyword : Hatchability, Ae. aegypti, Domestic Sewage Water